Time‐series properties and predictability of Greek exchange rates - Koutmos, Gregory; Theodossiou, Panayiotis (My University, 1994)
This paper explores the time‐series properties and predictability of weekly percentage changes in the Greek drachma exchange rates with respect to the currencies of major trading‐partner countries, such as the USA, Germany, the UK, France, Italy and Japan. The analysis is carried out using the EGARCH‐M model along with the power exponential distribution. Percentage changes in the Greek drachma with respect to the German mark, the French franc, the Italian lira and Japanese yen are predictable using past information. The volatility of Greek exchange rates is best represented by an EGARCH process and as such is predictable using past volatility measures. Moreover, volatility of the Greek drachma with respect to the German mark and Italian lira positively influences future movements in these exchange rates. The hypothesis that volatility is an asymmetric function of past innovations is rejected in all cases. Following the inclusion of the Greek drachma in the ECU currency basket, its value has been depreciating at a higher rate with respect to the German mark and Italian lira and at a lower rate with respect to the US dollar. Also, its volatility with respect to the German mark, the French franc, and the Italian lira has decreased, whereas its volatility with respect to the US dollar has increased.